2009
DOI: 10.1111/j.1741-2358.2008.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an oral function promotion programme for the independent elderly in Japan

Abstract: An oral function promotion programme was effective in improving the oral health status and oral function of an independent elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 26 publications
3
82
0
3
Order By: Relevance
“…For example, Hakuta et al reported that 'gargling' with water everyday reduced the tongue coating of the elderly subjects in her study of oral function [45]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, Hakuta et al reported that 'gargling' with water everyday reduced the tongue coating of the elderly subjects in her study of oral function [45]. …”
Section: Discussionmentioning
confidence: 99%
“…The study by Hakuta et al 27 obtained excellent results with an oral functionality promotion program for the elderly. This consisted of six sessions of exercises of the facial muscles, tongue and salivary gland massage, with two sessions per month for three months.…”
Section: Discussionmentioning
confidence: 97%
“…Impairment of these functions reduces masticatory efficacy, increases the risk of nutritional deficiencies, and decreases the pleasure of eating and communicating. These factors all influence the quality of life of the elderly and can lead to social isolation 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…구강기능 입체조는 일본에서 구강건강 증진을 위하여 구강기능 향 상 운동을 적용한 사업 [11]으로, 그 결과 입체조 프로그램 은 노인의 구강건강을 향상시키며 [12][13][14], 특히 고령화 및 초고령화 시대 노인의 구강건강을 증진시키는데 아주 효율 적이라고 보고하였다. 또한 이는 부작용이 없을 뿐만 아니 라 경제적 부담이나 시간과 장소의 제약 없이 노인들에게 지속적으로 활용이 가능한 운동이라고 보고 하였다 [8][9][10].…”
unclassified